(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the changes taking place in the socio-domestic life of the population of the villages of Surkhandarya region. The author studied the development processes in the fields of living standards, social services, employment, education and healthcare in rural areas, and highlighted existing problems and ways to eliminate them. The article also presents ideas on the development of infrastructure in villages, the introduction of modern technologies, and the impact of government programs on the lives of the population. The results of the study include scientific and practical recommendations on improving the well-being of the population in the villages of Surkhandarya region